2001
DOI: 10.1034/j.1600-0412.2001.080004311.x
|View full text |Cite
|
Sign up to set email alerts
|

Warm tub bathing during labor: maternal and neonatal effects

Abstract: Aim. To study possible detrimental maternal and neonatal effects of immersion in warm water during labor. Design. Prospective randomized controlled bathing during first stage of labor vs no bathing. Setting. Obstetrical departments at a university hospital and two central hospitals. Primary end-point. Referral of newborns to NICU. Material and methods. Randomization took place by means of sealed opaque envelopes at each delivery unit. Preconditions for participation in the study were: singleton parturient wish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
1
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 10 publications
0
55
1
4
Order By: Relevance
“…After the 1990s, when the WHO included the immersion bath as an NPM to be used during labor, there was increased interest in generating sufficient evidence to support this practice. During the last two decades, most of randomized clinical trials have evaluated immersion baths (Cluett, Pickering, Getliffe, & James, 2004;Ohlsson et al, 2001;Rush et al, 1996; Silva, Oliveira, & Nobre, 2009) and some controlled clinical trial of therapeutic intervention type rated aspersion showers (Davim et al, 2008;Santana et al, 2013), pointing to several benefits, among which are higher levels of satisfaction with the labor experience and pain relief, as long as certain conditions, such as a minimum dilation of 3 centimeters, are met before initiating its application. Although warm showers followed by breathing techniques and changes in position were the most commonly used NPMs (Table 1), having generated high levels of satisfaction, the method that actually produced the highest degree of satisfaction was focused attention, followed by the birth ball (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…After the 1990s, when the WHO included the immersion bath as an NPM to be used during labor, there was increased interest in generating sufficient evidence to support this practice. During the last two decades, most of randomized clinical trials have evaluated immersion baths (Cluett, Pickering, Getliffe, & James, 2004;Ohlsson et al, 2001;Rush et al, 1996; Silva, Oliveira, & Nobre, 2009) and some controlled clinical trial of therapeutic intervention type rated aspersion showers (Davim et al, 2008;Santana et al, 2013), pointing to several benefits, among which are higher levels of satisfaction with the labor experience and pain relief, as long as certain conditions, such as a minimum dilation of 3 centimeters, are met before initiating its application. Although warm showers followed by breathing techniques and changes in position were the most commonly used NPMs (Table 1), having generated high levels of satisfaction, the method that actually produced the highest degree of satisfaction was focused attention, followed by the birth ball (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, three of the admissions to the neonatal unit were between nine and 48 hours after delivery, while the three admissions immediately after birth were associated with temperature regulation. Comparative studies of labour in water found no increase in admissions to neonatal units or other markers of neonatal distress 2325. It is clearly important to ensure ongoing audit of neonatal outcomes for women who labour in water.…”
Section: Discussionmentioning
confidence: 99%
“…Benefits to women of labouring in water include buoyancy and ease of movement facilitating women to maximise pelvic diameters which may lead to improved fetal flexion and easier delivery [8]. The warm water increases maternal relaxation reducing pain perception [9], and may lead to improved uterine perfusion and reduced blood pressure [10].…”
Section: Introductionmentioning
confidence: 99%